Agronomic performance and drought tolerance level of sweet potato hybrids grown in Kupang, East Nusa Tenggara, Indonesia - YOSEP S. MAU; ANTONIUS S.S. NDIWA; JENNY E.R. MARKUS; I G.B. ADWITA ARSA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mau YS, Ndiwa ASS, Markus JER, Arsa IGBA. 2019. Agronomic performance and drought tolerance level of sweet potato hybrids grown in Kupang, East Nusa Tenggara, Indonesia. Biodiversitas 20: 2187-2196. This study was conducted to evaluate agronomic performance and to assess drought tolerance level of purple and orange-fleshed F1 sweet potato hybrids in dryland during dry season in Kupang, East Nusa Tenggara. The study was carried out in Integrated Archipelagic Dryland Field Laboratory of Universitas Nusa Cendana, Kupang, from May to October 2018. Two sets of experiment were conducted, the first was for evaluation of agronomic performance, and the second was for evaluation of drought tolerance of the sweet potato genotypes. The first experiment assessed the agronomic performance of 20 sweet potato genotypes in a Randomized Block Design. The second experiment employed a Split Plot Design consisted of irrigation level as the main plot and sweet potato genotypes as subplot treatments. The main plot consisted of no stress (normal) and water-stressed conditions while the sub-plot comprised of 20 genotypes of the sweet potato. The observed agronomic performance variables included growth and yield parameters. Tuber yields in no stress and water-stressed conditions were observed and used for assessment of drought tolerance. The results showed that, in the agronomic performance experiment, the sweet potato genotypes differed significantly in all the observed agronomic performance variables including growth, yield contributing, and yield variables. UNC2016.Cil/JPV.01 and UNC2016.Cil/JPV.05 were short maturing genotypes with only about 90 days to harvesting while the rest of the genotypes were harvested in 120 to 150 days. The genotypes were also significantly varied in tuber yield; the highest was observed in UNC2016.JPV/KDL.11 (43.38 t ha-1). In the drought tolerance evaluation experiment, tuber yields in no stress and stressed condition were, respectively, 23.42 t ha-1 and 7.08 t ha-1. Six F1 hybrids were classified and selected as drought-tolerant genotypes with high yielding performance in both no stress and water-stressed conditions.